MicroRNA-195: a review of its role in cancers - Yu, Wanpeng (Onco Targets Ther, 2018)
MicroRNAs (miRNAs) are small and highly conserved noncoding RNAs that regulate gene expression at the posttranscriptional level by binding to the 3′-UTR of target mRNAs. Recently, increasing evidence has highlighted their profound roles in various pathological processes, including human cancers. Deregulated miRNAs function as either oncogenes or tumor suppressor genes in multiple cancer types. Among them, miR-195 has been reported to significantly impact oncogenicity in various neoplasms by binding to critical genes and signaling pathways, enhancing or inhibiting the progression of cancers. In this review, we focus on the expression of miR-195 in regulatory mechanisms and tumor biological processes and discuss the future potential therapeutic implications of diverse types of human malignancies.